The first precinctive Carabidae from Moorea, Society Islands: new Mecyclothorax spp. (Coleoptera) from the summit of Mont Tohiea - Liebherr, James K. (Pensoft Publishers, 2012)

(untitled)
Abstract. Seven species of Mecyclothorax Sharp from Moorea, Society Islands are newly described; Mecyclothorax perraulti sp. n., Mecyclothorax pahere sp. n., Mecyclothorax menemene sp. n., Mecyclothorax mahatahi sp. n., Mecyclothorax popotioaoa sp. n., Mecyclothorax mapo sp. n., and Mecyclothorax fatata sp. n. These constitute the first Mecyclothorax species described from Moorea, and the first carabid beetle species shown to be geographically restricted to that island. Each of the newly described species is most similar to a different species on the island of Tahiti, suggesting that none of the seven Moorean taxa are evolutionary end-products of autochthonous speciation within Moorea. The occurrence of precinctive Mecyclothorax species on both Moorea and Tahiti demonstrates that radiation of Mecyclothorax in the Society Islands has been facilitated by speciation events implicating both islands. Whether this speciation has been preceded by vicariance or dispersal is discussed, with the generality of a dispersal hypothesis tested using information from Society Island Nabidae (Hemiptera). Salient morphological characters for taxa in the Society and Hawaiian Islands are compared to those representing a broad survey of southwest Pacific Mecyclothorax spp. This comparison supports the independent founding of each radiation in the Societies and Hawaii from an Australian ancestral propagule, likely drawn from the ecologically general, geographically widespread Mecyclothorax punctipennis (Macleay).